A performance comparison of two (electro) chemiluminescence immunoassays for detection and quantitation of serum anti‐spike antibodies according to SARS‐CoV‐2 vaccination and infections status. Issue 1 (19th December 2022) - Camacho, Jorge; Albert, Eliseo; Zulaica, Joao; Álvarez‐Rodríguez, Beatriz; Rusu, Luciana; Olea, Beatriz; Alcaraz, María Jesús; Geller, Ron; Giménez, Estela; Navarro, David
Abstract: The information provided by SARS‐CoV‐2 spike (S)‐targeting immunoassays can be instrumental in clinical‐decision making. We compared the performance of the Elecsys® Anti‐SARS‐CoV‐2 S assay (Roche Diagnostics) and the LIAISON® SARS‐CoV‐2 TrimericS IgG assay (DiaSorin) using a total of 1176 sera from 797 individuals, of which 286 were from vaccinated‐SARS‐CoV‐2/experienced (Vac‐Ex), 581 from vaccinated/naïve (Vac‐N), 147 from unvaccinated/experienced (Unvac‐Ex), and 162 from unvaccinated/naïve (Unvac‐N) individuals. The Roche assay returned a higher number of positive results (907 vs. 790; p  = 0.45; overall sensitivity: 89.3% vs. 77.6%). The concordance between results provided by the two immunoassays was higher for sera from Vac‐N ( ϰ : 0.58; interquartile ranges [IQR]: 0.50−0.65) than for sera from Vac‐Ex ( ϰ : 0.19; IQR: −0.14 to 0.52) or Unvac‐Ex ( ϰ : 0.18; IQR: 0.06−0.30). Discordant results occurred more frequently among sera from Unvac‐Ex (34.7%) followed by Vac‐N (14.6%) and Vac‐Ex (2.7%). Antibody levels quantified by both immunoassays were not significantly different when <250 ( p  = 0.87) or <1000 BAU/ml ( p  = 0.13); in contrast, for sera ≥1000 BAU/ml, the Roche assay returned significantly higher values than the DiaSorin assay ( p  < 0.008). Neutralizing antibody titers (NtAb) were measured in 127 sera from Vac‐Ex or Vac‐N using a S‐pseudotyped virus neutralization assay of Wuhan‐Hu‐1, Omicron BA.1, and Omicron BA.2. The correlation between antibody levels and NtAb titers was higher for sera from Vac‐N than those from Vac‐Ex, irrespective of the (sub)variant considered. In conclusion, neither qualitative nor quantitative results returned by both immunoassays are interchangeable. The performance of both assays was found to be greatly influenced by the vaccination and SARS‐CoV‐2 infection status of individuals.